Radiation Processing of Polymers for Medical and Pharmaceutical Applications. Issue 1 (July 2015) - Darwis, Darmawan; Erizal; Abbas, B.; Nurlidar, Farah; Putra, D. Pribadi; Haryono, Agus; Azuma, Jun‐ichi
Summary The use of ionizing radiation for the preparation of polymeric biomaterials is one of the examples of the application of atomic energy for the benefit of humanity. Radiation processing is based on the use of high energy ionizing radiation to induce chemical and biological changes in irradiated systems. High energy electron (EB) under 10 keV and gamma irradiation are the most frequently used of ionizing radiation for synthesis, modification of polymers, and sterilization of medical devices. Potential biomedical and pharmaceutical applications of these polymers are implants, topical dressings, injectable formulations, drug delivery devices, diagnostic assays, and immobilized enzyme. Through radiation crosslinking or degradation processes, polymers with specific characteristics can be prepared. The advantages of radiation processing include the absent of any chemical residues (since no chemical additives are requires to initiate the reactions), can be used at all temperatures, can be limited to the surface only and in certain cases, the synthesis/modification of materials can be combined with sterilization.